(3cTa GdUdUdI Yf hUa GdRdRdIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ dg gPg ahGFO eaUdI ?? eG hQO aj MbjbJgG CNQL CHh GdTjN Hf MHGf aj cJGH GdYXeI hGHf CHj GdOfjG aj cJGH GdYbhHGJ Yf GHf YHGS QVj Gddg YfgeG bGd Ndb Gddg LHdG jbGd dg bGa eMjW HGdYGdes
(3BNQgG (B:s
(3PcQ GdRdRdI GdJj JbY YfO NQhL GdOLGd CNQLO GdHZhj aj eYLe GdUMGHI hGdMGce aj GdeSJOQc hUMMg YfO eMLf Hf GdCOQY Cf QShd Gddg Udi Gddg Ydjg hSde NWH GdfGS abGd (B: (3jhe GdNdGU heG jhe GdNdGU KdGK eQGJ abjd jG QShd Gddg eG jhe GdNdGU hPdc jhe GdNdGUs
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B2\1491s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs